The association between low back pain and quality of life among Health Sciences Students/ Maizatul Naqiah Z ... [et al.] - Z, Maizatul Naqiah; Mohd Saat, Nur Zakiah; Hanawi, Siti Aishah; MI, Janet Bong; P, Lishantini; S, Tatiana; EW, Tan (Faculty of Medicine, 2023)
Introduction: Low back pain (LBP) is a growing public health problem that can affect anybody. However, little is known regarding the quality of life (QOL) of university students in Malaysia as consequences of LBP, especially among Health Sciences students. The goal of this study was to determine the association between QOL and LBP among Health Sciences students. Methods: Through convenience sampling, 96 Health Sciences students from a Malaysian university were included in this cross-sectional survey. The Oswestry Disability Index (OSW) Questionnaire and the Short-form 36 Questionnaire (SF-36) were used to collect the data. Results: According to the findings of this study, 93.8 percent (n=90) of the students had mild LBP, whereas 6.2 percent (n=6) had moderate LBP. There were no significant mean variations in LBP by gender, age, or course type (p>0.05). This study, however, discovered a significant negative relationship between all dimensions of QOL (general health, physical, and social function) and LBP disability (r=-0.24 to -0.40), p<0.05. This indicated that the students with a higher QOL score experienced less LBP. Conclusion: Finally, this research found a significant negative correlation between QOL and LBP in terms of general health physical function, and social function.